2020
DOI: 10.3389/fphar.2020.00485
|View full text |Cite
|
Sign up to set email alerts
|

Kunxian Capsule for Rheumatoid Arthritis: Inhibition of Inflammatory Network and Reducing Adverse Reactions Through Drug Matching

Abstract: Tripterygium wilfordii Hook.f and Tripterygium hypoglaucum (H.Lév.) Hutch is effective herbs to prevent aggravation of Rheumatoid arthritis (RA). However, both of them show severe side effects in the reproductive system and other systems. Kunxian Capsule (KX), a Traditional Chinese Medicine (TCM) patent prescription, comprised of 4 herbs, including H.Lév. Hutch, is reported to be an available prescription in treating RA with fewer side effects as compares to Tripterygium tablets. To reveal the pharmacological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 51 publications
2
29
0
1
Order By: Relevance
“…Our previous research using a bioinformatics approach demonstrated that Kunxian Capsule (a Traditional Chinese Medicine (TCM) patent prescription mainly comprises Levl. Hutch) could target at PI3K/AKT/mTOR signaling pathway ( Tang et al., 2020 ). Therefore, we speculate that some proteins in the PI3K-AKT-mTOR signal pathway are the most likely direct targets of tripterygium ingredients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous research using a bioinformatics approach demonstrated that Kunxian Capsule (a Traditional Chinese Medicine (TCM) patent prescription mainly comprises Levl. Hutch) could target at PI3K/AKT/mTOR signaling pathway ( Tang et al., 2020 ). Therefore, we speculate that some proteins in the PI3K-AKT-mTOR signal pathway are the most likely direct targets of tripterygium ingredients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the AEs of tripterygium ingredients could be due to the inhibition of NF-κB and PI3K pathways. Ameliorating AEs through drug matching may be a feasible strategy ( Tang et al., 2020 ). For example, some Chinese researchers matched the TwHf with Cistanche deserticola Ma or Cuscuta chinensis Lam , to reduce the reproductive toxicity of TwHf ( Dong et al., 2009 ; Jing and He, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The current work investigated the potential mechanisms of the curative effect of KC, a Chinese patent medicine, against RA, by integrating the chemical profiling with network pharmacology analysis, for the first time [ 6 , 41 ]. The establishment of TCM-herb-ingredient-target-pathway network could make a useful reference for further drug development and the treatment of RA.…”
Section: Discussionmentioning
confidence: 99%
“…Triptolide has been shown to inhibit the phosphorylation of PI3K and AKT in bone marrow mononuclear cells [ 43 ], to decrease the phosphorylation of JAK and STAT in the human leukemic U937 cells and in collagen-induced arthritis rats [ 44 ], and to inhibit the activation of matrix metalloproteinase 9 (MMP-9). Moreover, KC could inhibit the excessive inflammatory response and regulate the immune reaction [ 6 ]. Icariin inhibited STAT3 activation in T cells, resulting in decreased IL-17 production and alleviated RA [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hopkins proposed the concept of “network pharmacology” and it’s becoming increasingly popular among researchers in recent years ( Tang et al, 2020 ; Xu J. et al, 2019b ). The characteristic of network pharmacology is following the holistic theory of TCM(S. He et al, 2019b ).…”
Section: Introductionmentioning
confidence: 99%